Remote ischaemic conditioning decreases blood flow and improves oxygen extraction in patients with early complex regional pain syndrome - Hegelmaier, Tobias Sebastian; Vollert, Jan (European journal of pain, 2017)
Background: Remote ischaemic conditioning (RIC) is the cyclic application of non-damaging ischaemia leading to an increased tissue perfusion, among others triggered by NO (monoxide). Complex regional pain syndrome (CRPS) is known to have vascular alterations such as increased blood shunting and decreased NO blood-levels, which in turn lead to decreased tissue perfusion. We therefore hypothesized that RIC could improve tissue perfusion in CRPS. Method: In this proof-of-concept study, RIC was applied in the following groups: in 21 patients with early CRPS with a clinical history less than a year, in 20 age/sex-matched controls and in 12 patients with unilateral nerve lesions via a tourniquet on the unaffected/non-dominant upper limb. Blood flow and tissue oxygen saturation (StO2) were assessed before, during and after RIC via laser Doppler and tissue spectroscopy on the affected extremity. The oxygen extraction fraction was calculated. Results: After RIC, blood flow declined in CRPS (p < 0.01). StO2 decreased in CRPS and healthy controls (p < 0.01). Only in CRPS, the oxygen extraction fraction correlated negatively with the decreasing blood flow (p < 0.05). Conclusion: Contrary to our expectations, RIC induced a decrease of blood flow in CRPS, which led to a revised hypothesis: the decrease of blood flow might be due to an anti-inflammatory effect that attenuates vascular disturbances and reduces blood shunting, thus improving oxygen extraction. Further studies could determine whether a repeated application of RIC leads to a reduced hypoxia in chronic CRPS. Significance: Remote ischaemic conditioning leads to a decrease of blood flow. This decrease inversely correlates with the oxygen extraction in patients with CRPS.